Stimulating game performance skills in students: experimental studies using net games - Harianto, Eko; Gustian, Uray; Supriatna, Eka; Shalaby, Mohammed Nader; Taiar, Redha (Universitas Tanjungpura, 2023)
Background and Study Aim. Game performance is the quality and quantity of a person in carrying out the game that has been given in accordance with the responsibilities and results specified. But so far, it is still rare to find research that discusses games performance. This study aims to determine whether the stimulation of elementary school students' game performance ability through net gamesMaterial and Methods. This research is a pre-experiment with a one-group pretest and posttest design. The sampling technique used purposive sampling so that 12 elementary school students could be obtained. In this study, students were given treatment in the form of net games. As for pretest and posttest data using instruments in the form of tests with rubrics, Data analysis uses Microsoft Excel 2019 and SPSS version 26 applications.Results. The results showed a significance value of 0.000 < 0.05, so the net game treatment had a significant effect on game performance. Furthermore, 16.7% were in effective performance, 58,3% were in moderately effective performance, and 25% were in weak performance. These results provide evidence that children are dominant and moderately effective.Conclusions.Based on these results, this study proves that net games can be used to stimulate game performance.